Diminished ability to integrate target stimuli with context during emotional recognition in individuals with broad autism phenotype - Cha, Woo-Jin; Lee, Jang-Han (Frontiers in Psychology, 2022)
Individuals with broad autism phenotype (BAP) have a tendency not to integrate emotional stimuli with the surrounding context. They have also shown different patterns and abilities in processing positive and negative emotions. This study aimed to examine whether the effect of context on target stimuli could vary, depending on the type of target emotion, in individuals with BAP. Based on the Broad Autism Phenotype Questionnaire (BAPQ) and Autism-Spectrum Quotient (AQ), 36 individuals with BAP and 33 healthy controls were selected. All participants performed an overlap-emotional task consisting of six conditions: 2 (congruence: congruent and incongruent) × 3 (emotion: fearful, sad, and happy). Reaction time and accuracy were measured as dependent variables. The results revealed that individuals with BAP showed no difference in reaction time between the condition of congruence and incongruence, but the control group was faster to categorize facial expression on the condition of congruence than that of incongruence, regardless of the type of target emotion. There were no differences between the two groups in any of the conditions with regard to accuracy. These findings indicate that individuals with BAP tend not to integrate target emotions with contextual information, a feature that could worsen the speed of emotional recognition in individuals with BAP. This study confirmed that individuals with BAP have different cognition patterns in emotional recognition than the control group.